Catalyst-free synthesis of 2, 3-dihydro-1, 5-benzothiazepines in a renewable and biodegradable reaction medium. (17th April 2019) - Yadav, Neetu; Yadav, Vijay B.; Ansari, Mohd Danish; Sagir, Hozeyfa; Verma, Ankit; Siddiqui, I. R.
Abstract : A clean and efficient strategy for the synthesis of benzothiazepines from chalcone and ortho -aminothiophenol has been reported. Abstract : A clean and efficient strategy for the synthesis of benzothiazepines from chalcone and ortho -aminothiophenol has been reported. Here, glycerol, a biodegradable and reusable promoting medium, has been utilized under acid, base or metal-free conditions. The significant features of the protocol include a one-pot eco-friendly approach, short reaction time, high atom economy, broad substrate scope, easy workup process and high yields.